Early to bed and earlier to rise: School, maternal employment, and children's sleep - Jay Charles Stewart (Institute for the Study of Labor (IZA), 2013)
School-age children need 10-11 hours of sleep per night. It has been well-documented that lack of sleep leads to diminished cognitive performance and that people who sleep less are more likely to be overweight or obese. I use data from the American Time Use Survey (ATUS) to examine two factors that can potentially influence the amount of time children sleep: school and maternal employment. I find that school-age children sleep less when school is in session than during the summer, and that they get less sleep on school nights than on non-school nights. Children go to bed about 38 minutes earlier on school nights, but wake up about 72 minutes earlier on school days. This translates into about 34 minutes less sleep on school nights compared with non-school nights, and implies that these children have a cumulative sleep deficit of over two-and-a-half hours by the time they arrive at school Friday morning. In addition to the lost sleep time, the earlier wake-up times on school days appear to disrupt children's natural sleep cycles. Maternal employment affects children's sleep time in the summer, because children wake up earlier on days that their mothers work. But during the school year, maternal employment effects are dominated by school effects.
Keywords: J22; 330; sleep; school start times; maternal employment; time use